MXene anchored nanostructured nickel phosphide as an efficient photocatalyst for the UV assisted photodegradation of reactive black-5 dye - Faheem, Muhammad; Fayyaz, Maria; Sohail, Manzar; Paiman, Suriati; Abbas, Syed Mustansar; Riaz, Asim (Elsevier B.V., 2026)
The development of a highly efficient, cost-effective and stable photocatalyst for the effective removal of organic pollutants from wastewater is still in demand for environmental remediation. Herein, novel Ni2P/MXene nano-composite has been synthesized via a facile hydrothermal method. The MXene sheets decorated with the Ni2P catalyst structures were characterized by X-ray Diffraction, Field emission scanning electron micrograph/EDX, Diffused Reflectance Spectroscopy respectively. Reactive Black 5 dye (RB-5) was used as a vital pollutant to evaluate photocatalytic efficiency. The synthesized structures shows excellent UV-driven photocatalytic activity, achieving nearly a 92% degradation of the organic contaminants using only half of the 2D Ni2P/MXene photocatalyst loading as compared to Ni2P nanoparticles. This activity enhancement is attributed to the combination of the prominent photocatalytic properties of Ni2P structures, which acts as a photogenerated electrons reservoir to enhance photoinduced charge separation, and the charge transfer facilitation by the MXene sheets due to a lower band gap of 1.51 eV in Ni2P /MXene catalyst as compared to ∼1.8 eV in Ni2P nanoparticles. These MXene-based nano-hybrids are a promising photocatalyst materials used for environmental applications.